2008
DOI: 10.1111/j.1365-2516.2008.01795.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, clinical features and molecular assessment of the dysfibrinogenaemias

Abstract: Hereditary dysfibrinogenaemia is characterized by the presence of functionally abnormal plasma fibrinogen. Dysfibrinogenaemia is a heterogeneous disorder associated with different mutations throughout the three genes that code for the fibrinogen sub-units, affecting many different aspects of fibrinogen/fibrin activity. Dysfibrinogenaemia may be discovered during the investigation of individuals who present with bleeding or thombosis, or may be found in individuals during routine coagulation screening. More spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 75 publications
1
36
0
1
Order By: Relevance
“…Hereditary dysfibrinogenaemias are caused by a variety of mutations in the three fibrinogen genes that code for its polypeptide chains and may be uncovered in patients who present with thrombosis or bleeding or may be discovered by routine coagulation testing (5, 6). Mutations can result in quantitative defects, such as afibrinogenaemia or hypofibrinogenaemia or qualitative defects resulting in functional deficiencies in the protein’s activities or a combination of both.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hereditary dysfibrinogenaemias are caused by a variety of mutations in the three fibrinogen genes that code for its polypeptide chains and may be uncovered in patients who present with thrombosis or bleeding or may be discovered by routine coagulation testing (5, 6). Mutations can result in quantitative defects, such as afibrinogenaemia or hypofibrinogenaemia or qualitative defects resulting in functional deficiencies in the protein’s activities or a combination of both.…”
mentioning
confidence: 99%
“…Studies of afibrinogenaemias have given us data about the synthesis, assembly, and secretion of fibrinogen (79), while investigation of qualitative dysfibrinogenaemias has provided a great deal of information on fibrin polymerisation, fibrinolysis, platelet aggregation, and other functions (2, 10, 11). Dysfibrinogenaemias can also give us clues about relationships between molecular structure/function and clinical consequences (5, 6). …”
mentioning
confidence: 99%
“…Hypodysfibrinogenemia is a rare disorder characterized by a reduced fibrinogen antigen level, associated with a disproportionately low functional activity . A systematic review of literature by Casini et al identified 51 index cases of hypodysfibrinogenemia with 32 causative mutations, clustered in the COOH‐terminal of the γ or the Aɑ chains .…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen, a 340 kDa glycoprotein, consists of three homologous polypeptide chains (Aɑ, Bß, and γ), encoded by FGA , FGB , and FGG genes, respectively, which are clustered on the long arm of chromosome 4 . Congenital fibrinogen disorders may be classified into quantitative deficiency (afibrinogenemia and hypofibrinogenemia) or qualitative defect (dysfibrinogenemia or hypodysfibrinogenemia) in the synthesized protein . Phenotypic manifestations include arterial and venous thrombotic events in addition to bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a bleeding or thrombotic phenotype is dependent on the underlying mutation. 88 One case report of ICH and cephalhematomas in a child with suspected dysfibrinogenemia has been published. The case in that report was unique in that the patient had a long history of bleeding and almost undetectable fibrinogen levels.…”
Section: Defects Of Fibrinogenmentioning
confidence: 99%